Improvised Protocol for Enhancement of Security in Internet of Vehicles - Kumar, Pranjul; Kaur, Sanmukh; Mehrotra, Deepti (International Journal of Sensors Wireless Communications and Control, 2022)
Background: Vehicular Ad-Hoc Network (VANET) is integral to lessen road mishappenings and to effortlessly control huge traffic on highways. Numerous protocols are researched and implemented for creating a secure medium between vehicular nodes. Objective: One of the visible problems is the loss of data between the nodes, which leads to delay, collision, and accidents in the VANET. This paper investigates traffic security and safety problems faced in VANET and provides a solution for them. Methods: For analyses of traffic safety issues, 3 types of Medium Access Control (MAC) protocols were compared, namely Conventional, Contention-Based and Contention-Free MAC Protocols. Plentiful of performance metrics have been studied under the transportation security issues, including signal received with error, throughput, and MAC Overhead and Packet loss. Results and Conclusion: By comparing the MAC Protocols, it can be concluded that Contention-Free multi-channel SD-TDMA is better with a security mechanism for continuous and safe communication between the vehicular nodes. It can be utilized in moderate to heavy traffic scenarios to have faster and safe communication.
Keywords: signal received with error